Introduction of peripheral nitrogen atoms to cyclo-meta-phenylenes - Koki Ikemoto; Hiroyuki Isobe (Beilstein Journal of Organic Chemistry, 2024)
Cyclo-meta-phenylenes doped with nitrogen atoms at the periphery were designed and synthesized. The syntheses of the macrocyclic structures were achieved with one-pot Suzuki–Miyaura coupling to arrange phenylene rings and pyridinylene rings in an alternating fashion. Analyses with UV–vis spectroscopy showed changes in the photophysical properties with nitrogen doping, and X-ray crystallographic analyses experimentally revealed the presence of biased charges on the peripheral nitrogen atoms.